An Introduction to Behaviourism, Innatism and Interactionism Theories of Language Acquisition: Literature Review - Shivan Mawlood Hussein (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
There are many theories that have influence on the field of second language acquisition, and all of the theories have different principles and ideas. The knowledge about theories, methods, approaches, strategies and techniques is essential in order to have effective language classes. However, many of the instructors and teachers have lack of information about the language theories based on a survey which has been conducted in a social media poll. The poll consisted of two basic questions which were: 1- Are you familiar with the language theories? 2- Have you studied language theories in your academic studies? The number of teachers who answered the questions were 63. The teachers are teaching from both the public sector and private sector. The result demonstrated that 58 of the teachers were not familiar with the theories of language. Moreover, 60 of the teachers confirmed that they have not studied language theories in their studies. Therefore, this study aims to introduce the language theories including Behaviourism, Innatism and Interactionism in addition to principles, strengths and weak points of each theory. The current study concluded that teachers have to familiarize themselves with the theories of language acquisition through reading books, reading articles and participating in the teacher development courses in order to make their classes more effective and influential.